Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN